The Effect of Treffinger Learning Model in Building Students' Creative Disposition in Elementary School Science Learning - Fitriana, Iin Mahlia; AA. Sukarso; Gunawan; Asrin; Sri Subarinah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This study aims to find and describe the effect of Treffinger learning model on students' creative disposition. The number of subjects in this study consisted of two class groups, namely the experimental class with a total of 20 students and the control class with a total of 24 students conducted at SDIT Generasi Muslim Cendekia. Data collection methods were carried out by means of documentation, observation, questionnaires and tests. The results of this study indicate the effect of Treffinger learning on the creative disposition of students in the experimental class group with the results of the creative disposition hypothesis test obtained an F value of 77.362 with a significance of 0.000Ë‚0.05, then Ho is rejected, so Ha is accepted. Based on the results of the analysis that the Treffinger learning model is proven to be able to improve the creative disposition of science of SDIT Generasi Muslim Cendekia students.